Measuring self-efficacy to deal with infertility: Psychometric properties and confirmatory factor analysis of the Portuguese version of the infertility self-efficacy scale - Galhardo, Ana (2013)
This study explores the psychometric properties and factor structure of the Portuguese version of the Infertility Self-Efficacy Scale (ISE-P), using translation and back-translation of the original version; principal component analysis; confirmatory factor analysis (CFA); and internal consistency, and test-retest reliability analyses. A total of 287 participants (156 women and 131 men) seeking medical treatment were recruited from public and private fertility centers. CFA revealed that the single-component model fit the data well. The instrument showed excellent internal consistency, good test-retest reliability, and correlations with other mental health measures suggesting good convergent and discriminant validity. In conclusion, The ISE-P is a valid and reliable Portuguese-language measure of perceived self-efficacy to cope with infertility.